Mobile-Assisted Language Learning (MALL) in Indonesia: Case on English Language Learning for Higher Students during COVID 19 - Ibrahim Ibrahim (Universitas Sembilanbelas November Kolaka, 2021)
The present paper, therefore, aims to develop deeper students’ understanding and perception regarding the use of mobile assisted language learning in the learning process. All schools and universities should eliminate offline learning and switch to online education. When this is enforced, not a few students find it difficult to access online learning. Some students may have privileges in the form of computers and internet access. This one can easily follow the learning delivered through online media used by the school/Learning management system.This study adopted qualitative research design where case study is used. In this study, the research participants are five students taken from university students who are currently taking English education. To hinder the ethical issues during the data collection and also the research process, the anonymity of the participants is implemented. The research participants also filled out the informed research consent form in order to share the agreement to be part of this study. There are some benefits gaining from implementing MALL such as learning flexibility and easiness. Students are not limited by the place and time to start studying and access some English sources. However, the comprehension supports for students from surrounding in mastering the technology use will enhance the learning process.